A SISTEM INFORMASI BERBASIS WEB UNTUK PEMBUATAN DAN PENGELOLAAN PORTOFOLIO PRIBADI - Batubara, Muhammad Sakban; Hutabarat, Purnama Helena (Informasi Interaktif : Jurnal Informatika dan Teknologi Informasi, 2026)
The swift of information technology has motivated numerous people—especially professionals, students, and scholars—to build their digital self-image. A personal portfolio is an effective way to showcase their identity, skills, and work. However, physical portfolios have several limitations, such as being difficult to access, difficult to distribute, difficult to update, less visually appealing, and requiring dedicated storage space. As a solution, a web-based personal portfolio is here to display professional data and individual work in a more structured, interactive, and easily accessible way via the internet. The purpose of this research is to develop and create a personal portfolio website that is responsive, interactive, and easy to use. The development approach used in this study follows  the waterfall model, encomassing the phases of requirements analysis, system design, implementation, and testing. The system was built utilizing PHP, HTML, CSS, and JavaScript programming languages, with a MySQL database as a storage medium. The findings of this research are a web-based personal portfolio creation information system that makes it easy for users to display personal data, educational history, work experience, projects, and skills in a professional and attractive manner. Furthermore, this system can reduce reliance on physical portfolios, which tend to be expensive and time-consuming to create. Data updates are also faster and more efficient. With this website, users are expected to build a professional image in the digital world and make it easier for others to recognize and assess their competencies more effectively.